Parasite protozoa of importance in public health picked up by Musca domestica Linnaeus in Lima, Peru - Cárdenas, Martín (2004)
At the present work we had investigated protozoa parasite picked up by Musca domestica. Surveys were carry out between June and December 1998 in districts of Lima (Comas and San Juan de Lurigancho). A total of 3014 flies were collected around garbage accumulated in the streets. Each survey were considered a lot with a mean of 30 flies. A total of 100 lots were studied. The flies were dissected and processed with sterilised distilled water for obtain the intestinal macerated. Observations were made by the simple direct method and with Gomori trichromic stain modified acid-fast. The following protozoa parasites of human were found: Blastocystis hominis (9,0%), Giardia lamblia (3,0%), Cryptosporidium sp. (2,0%), Cyclospora cayetanensis (1,0%), Iodamoeba bütschlii (17,0%), Endolimax nana (5,0%) and Chilomastix mesnili (3,0%). B. hominis y Cyclospora cayetanensis were reported for the first time in M. domestica from Peru.